(untitled) (Papeles, 2024)
Introduction: Gamification is presented as a tool that offers potential solutions to the decline in student motivation. However, the current evidence base is inconclusive and presents discrepancies, which makes it challenging for educators who wish to implement it to identify critical sources of information. In light of the aforementioned considerations, we propose to undertake a narrative review with the objective of elucidating the current status of gamification, as well as developing and analysing the various trends it addresses, the most prevalent errors, aspects pertaining to the elements of the game, adaptive gamification, gamification in physical education and the relationship between this strategy and the psychological theories that underpin it. Methodology: A search was conducted in the databases of Web of Science, Scopus, ERIC, PubMed, SciELO and Dialnet. A total of 64 articles were included in the review. Results and Discussion: The results provide teachers with knowledge about psychological theories and a use of gamification taking into account existing game element systems. Furthermore, adaptive gamification is postulated as a growing trend, taking into account the individual needs and profiles of players. In physical education, positive results towards a healthy lifestyle are observed, especially in students with little predisposition for physical activity. Conclusions: Gamification is a potentially interesting tool that can have positive effects on motivational variables if the basic knowledge about it is available, although caution and a critical spirit are required in its implementation.